2004
DOI: 10.1899/0887-3593(2004)023<0198:trofip>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The role of floods in particulate organic matter dynamics of a southern Appalachian river–floodplain ecosystem

Abstract: We investigated the effect of a flood on particulate organic matter (POM) dynamics in the floodplain and active channel of the Little Tennessee River in western North Carolina. We measured litterfall, leaf breakdown, and floodplain litter (before and after the flood) at 12 sites. Annual litterfall (256-562 g m 2 y 1) was typical of a temperate deciduous forest but lower than lowland floodplain forests in the eastern US. Leaf breakdown rates of 4 tree species (Acer rubrum, Carpinus caroliniana, Juglans nigra, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
2
28
0
1
Order By: Relevance
“…Minshall et al (1983) observed longitudinal increases of similar magnitude in GPP, but these were measured across larger changes in stream size. Meyer and Edwards (1990) showed a remarkably similar increase from 4th-order Black Creek, Georgia, to 6th-order Ogeechee River, Georgia, sites with Neatrour (1999) at sites near river metabolism sites. Percent of total input is in parentheses below input values.…”
Section: Longitudinal Trends In Metabolismmentioning
confidence: 66%
See 2 more Smart Citations
“…Minshall et al (1983) observed longitudinal increases of similar magnitude in GPP, but these were measured across larger changes in stream size. Meyer and Edwards (1990) showed a remarkably similar increase from 4th-order Black Creek, Georgia, to 6th-order Ogeechee River, Georgia, sites with Neatrour (1999) at sites near river metabolism sites. Percent of total input is in parentheses below input values.…”
Section: Longitudinal Trends In Metabolismmentioning
confidence: 66%
“…Direct litterfall input to the river decreased per unit area as the river got larger. Flood input of CPOM ranged from 16.2 g C m Ϫ2 y Ϫ1 at site 2 to 26.8 g C m Ϫ2 y Ϫ1 at site 1, but input varied dramatically because of differential inundation and entrainment (Neatrour 1999). Annual respiratory loss of C was highest at site 1 (522.7 g C m Ϫ2 y Ϫ1 ) and lowest at site 3 (384.5 g C m Ϫ2 y Ϫ1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased CPOM input, decreased herbaceous input, and increased leaf and woody input occurred as the composition of the riparian habitat shifted from herbaceous riparian habitat to a mixed herbaceous-shrub riparian habitat to forested riparian habitat along a prairie stream in Kansas [37] and along a fifth order stream in Idaho [4]. Neatrour et al [8] documented that reductions in riparian forest width as result of agriculture led to decreases in tree density and CPOM inputs within riparian habitats adjacent to a small river in North Carolina. Sites with < 5 m forested riparian widths had less tree density and less CPOM input than sites having forested riparian widths > 5 m [8].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted all statistical analyses using Statistical Analysis System (version 9.1, SAS Institute, Cary, North Carolina). We used an analysis of covariance (ANCOVA) with a dummy variable to make comparisons in breakdown rates between species, between single-and mixed-species packs, and among streams (Neatrour et al 2004). To make pairwise comparisons in breakdown rates, we controlled the false discovery rate (i.e., the fraction of rejected null hypotheses) to reduce inflation of the Type 1 error rate resulting from multiple pairwise comparisons (Bejamini and Hochberg 1995).…”
Section: Discussionmentioning
confidence: 99%